PENGARUH BAURAN PEMASARAN TERHADAP LOYALITAS KONSUMEN DI SWALAYAN PEPSI JAYA - Ahmad Dardiri (Jurnal Sumber Daya Manusia Unggul (JSDMU), 2021)
In order to carry out this type of self-service market, there are many things that must be considered, not only planning but also how to make a design / shape that aims to maintain the self-service business, so that it is not only how the supermarket is able to provide various forms and types of goods needed.Provide input to supermarket managers on aspects related to the marketing mix and customer loyalty that must be addressed based on the priority scale in order to encourage customer satisfaction levels and sales turnover growth.Based on the test results, it is known that the marketing mix has a positive effect on consumer loyalty, meaning that any increase in the marketing mix will increase consumer loyalty. If there is a decrease in the marketing mix, consumer loyalty will decrease. This is reinforced and supported by the sig value. smaller than the alpha value, namely 0.040 <0.05, it means that the marketing mix has a positive and significant effect on consumer loyalty. Furthermore, it can be seen that the results of t count is greater than t table, namely 2,795> 2,021, meaning that H0 is rejected and Ha is accepted. So this shows that the marketing mix in Pepsi Jaya Supermarkets has a positive and significant effect on consumer loyalty. The results of this study are supported by empirical evidence from previous research researched by Ocky Dwi Putranto (2016). The results of this study indicate that the retail marketing mix has a significant positive effect on customer loyalty at Lenmarc Mall Surabaya.